2021
DOI: 10.1515/nanoph-2021-0207
|View full text |Cite
|
Sign up to set email alerts
|

Smart NIR-light and pH responsive doxorubicin-loaded GNRs@SBA-15-SH nanocomposite for chemo-photothermal therapy of cancer

Abstract: We designed novel biocompatible nanocomposite composed of gold nanorods coated with rod-like mesoporous silica SBA-15-SH particles, (GNRs@SBA-15-SH) as a new synergistic therapeutic device to deliver heat and drug to cancer cells for tumor eradication. For this purpose, doxorubicin (DOX) was loaded into GNRs@SBA-15-SH nanocomposites and studied their photothermal therapy, chemotherapy and the combined effect on the ablation of A549 cells in vitro using human lung cancer cells, A549. The results demonstrate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 69 publications
0
16
1
Order By: Relevance
“…Therefore, the use of two methods or different types of methods of treatment or a method to boost another method of treatment has developed a new trend in cancer treatment . The combination of chemotherapy and photothermal therapy can be more effective than single therapy because hyperthermia was exhibited to result in higher and faster drug release into a tumor, and improvement of the anticancer effect of chemotherapeutic drugs such as doxorubicin. , Therefore, gold nanorods coated with DNA, proteins, stimulus-responsive polymers, porous metal organic frameworks, and porous silica with large loading capacities have been expanded to assess the effect of photothermal-chemotherapy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of two methods or different types of methods of treatment or a method to boost another method of treatment has developed a new trend in cancer treatment . The combination of chemotherapy and photothermal therapy can be more effective than single therapy because hyperthermia was exhibited to result in higher and faster drug release into a tumor, and improvement of the anticancer effect of chemotherapeutic drugs such as doxorubicin. , Therefore, gold nanorods coated with DNA, proteins, stimulus-responsive polymers, porous metal organic frameworks, and porous silica with large loading capacities have been expanded to assess the effect of photothermal-chemotherapy …”
Section: Introductionmentioning
confidence: 99%
“…20 The combination of chemotherapy and photothermal therapy can be more effective than single therapy because hyperthermia was exhibited to result in higher and faster drug release into a tumor, 21 and improvement of the anticancer effect of chemotherapeutic drugs such as doxorubicin. 22,23 Therefore, gold nanorods coated with DNA, proteins, stimulus-responsive polymers, porous metal organic frameworks, and porous silica with large loading capacities have been expanded to assess the effect of photothermal-chemotherapy. 24 The key to chemo-photothermal combined therapy depends on the photothermal agents; photothermal therapy (PTT) can be acquired simultaneously with laser light irradiation, leading to chemo-photothermal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Dox-AuNPs nanocomposite was made according to Vaithilingam method [ 16 ]. 1 ml of different concentrations of Dox (10, 20, 30, 40 μM) were mixed drop-wise with 1 ml of 0.125 mM of AuNPs with continues stirring and sonicate for 10 min until deep red becomes blue.…”
Section: Methodsmentioning
confidence: 99%
“…Excitingly, PTT mediated by silica core/gold shell "nanoshells" (also known as auroshells) has entered human clinical trials, with promising results reported [5][6][7]. Moreover, preclinical studies have shown that PTT can greatly enhance the efficacy of chemotherapy [8][9][10][11], radiotherapy [12][13][14] and immunotherapy [15,16] when deployed in tandem, indicating PTT has great promise to improve patient care in the decades to come.…”
Section: Overview Of Photothermal Therapy (Ptt) As a Cancer Treatment...mentioning
confidence: 99%